Analisis Rasio Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021 - Rensa U br. Ginting; Matius Nainggolan; Ike Rukmana Sari; Munawarah Munawarah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of the Current Ratio, Debt to Asset Ratio, Working Capital Turnover, Return on Assets and Earning per Share can affect Stock Returns in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The population of this study were 38 companies with a sample determination using purposive sampling method, obtained 22 samples during 3 years of observation into 66 data to be processed and analyzed. The results of the study simultaneously Current Ratio, Debt to Asset Ratio, Working Capital Turnover, Return on Assets and Earning per Shares have a significant influence on Stock Return of 28.9%. Partially, Working Capital Turnover has a positive and significant effect on Stock Return. Meanwhile Current Ratio, Debt to Asset Ratio, Return on Assets and Earning per Shares do not significantly influence Stock Returns Keywords: Current Ratio; Debt to Asset Ratio;...Earning On Asset; Return on Asset; Stock Returns; Working CapitalTurnover